Modulation of consciousness in disorders of consciousness by HD-tDCS targeting frontal and posterior cortical regions - Yongkun Guo; Yuan Zhong; Anqin Dong; Wanqing Liu; Shuai Han; Kang Zhang; Jingwei Xie; Pengyuan Zheng; Yihua Wang; Chunyun Zhang (Scientific Reports)
Abstract The search for neural correlates of consciousness has always been a hot topic in the field of consciousness. Previous studies have shown that high-density transcranial direct current stimulation (HD-tDCS) can promote the recovery of consciousness level in patients with disorders of consciousness (DOC). This study intends to explore the neuromodulatory effects of HD-tDCS at different target from the perspectives of brain spatiotemporal dynamics and directed information flow, thereby clarifying the key brain areas for the origin of consciousness. The study prospectively used a high-density transcranial direct current stimulation (HD-tDCS) protocol to perform repeated stimulation at different target points for 46 DOC patients (F3 group, n = 11; sham group, n = 19; Pz group, n = 16). The Coma Recovery Scale-Revised (CRS-R) index was calculated, and microstate analysis and symbolic transfer entropy(STE) brain network construction were performed before and 14 days after HD-tDCS stimulation. We identified seven microstates with different spatial distributions of electrode activation. There were significant differences in microstates (including spatial activation patterns and brain dynamics) for different stimulation protocols. At the same time, the F3 group strengthened the information flow from the anterior to the posterior brain and internal information flow in the anterior brain in the theta band, while the Pz group mainly increased the information flow between the left frontal and parietal lobes in the theta and alpha bands. The study suggests that consciousness is the result of the comprehensive action of the anterior and posterior brain, and there is an overlap in the mechanisms of action between the two HD-tDCS stimulation protocols, suggesting that a multi-target combined stimulation protocol may be a potentially better stimulation scheme.